Design and Experimental Evaluation of a Vehicular Network Based on NEMO and MANET. (15th September 2010) - Tsukada, Manabu; Santa, José; Mehani, Olivier; Khaled, Yacine; Ernst, Thierry
Abstract : Mobile Ad hoc Network (MANET) routing protocols and Network Mobility (NEMO) Basic Support are considered key technologies for vehicular networks. MANEMO, that is, the combination of MANET (for infrastructureless communications) and NEMO (for infrastructure-based communications) offers a number of benefits, such as route optimization or multihoming. With the aim of assessing the benefits of this synergy, this paper presents a policy-based solution to distribute traffic among multiple paths to improve the overall performance of a vehicular network. An integral vehicular communication testbed has been developed to carry out field trials. First, the performance of the Optimized Link State Routing protocol (OLSR) is evaluated in a vehicular network with up to four vehicles. To analyze the impact of the vehicles' position and movement on network performances, an integrated evaluation environment called AnaVANET has been developed. Performance results have been geolocated using GPS information. Second, by switching from NEMO to MANET, routes between vehicles are optimized, and the final performance is improved in terms of latency and bandwidth. Our experimental results show that the network operation is further improved with simultaneous usage of NEMO and MANET.